AVAILABILITY OF RAW MATERIAL, NUTRIENTS CONTENT, PROBIOTIC POTENCIAL AND SHELF LIFE OF REJANG LEBONG’S SALTED MUSTARD AS AN AGROINDUSTRY PRODUCT - Wuri Marsigit; Helmiyetti Helmiyetti (BPFP Faperta UNIB, 2018)
The Purpose of this study was to reveal the availability as the a raw material, its nutrient content, its probiotic, shelf life of salted mustard in Rejang Lebong Regency to be developed into agroindustry product. Primary data were collected by using structured questionair to the farmer, the group of farmer, the group farmer association, BPP, the stackholders, fields observation and laboratory analysis. Secondary data were gahthered from literature, government public service, institution, and other stackholders. Data collected were tabulated and analysed descriptively. Data of laboratory measurement were analysed by one-way Anova (?, 005). The result of study found that the existing raw material was available in qualitively, quantitively and continously. The price of bit mustard as a raw material was Rp. 1000 to Rp.7000 per kg. Salted mustard was rich of carbohydrate, protein, fiber, vitamin C, calcium, kalium, phosphorus, iron and magnesium. Nutrients content were not decrease, except vitaminc during storaging 0, 3, and 6 months, however Total Plate Count (TPC) tend to decrease. The price of salted mustard were Rp. 130.000 per kg or Rp. 13.000 per 100 g.